The Effect of Service Quality, Structural Empowerment, and Safety Culture On Nurse Job Satisfaction in Indonesia - I Made Raditya Mahardika; Sandra Dewi; Pamungkas, Rian Adi (International Journal of Nursing and Health Services (IJNHS), 2022)
Background: Job satisfaction is an emotional response to various aspects of work. If the rights of nurses are fulfilled, it will impact optimal nursing care to patients. Purpose: The purpose of this study was to analyze the effect of service quality, structural empowerment, and patient safety culture on nurse job satisfaction. Method: Cross-Sectional approach is used in this research. This study involved 172 nurses. Result: The implementation of service quality, structural empowerment, and safety culture significantly positively affect nurse job satisfaction. Conclusion: The implementation of service quality, structural empowerment, and safety culture both partially and simultaneously have a significant positive impact on nurse job satisfaction. Recommendation: Further researcher need to consider other factors could influence the job satisfaction among nurses. The Structure Equation Modelling also need to consider by the further researcher to test the direct and indirect effect of job satisfaction